The Impact of Oil Price Uncertainty on Stock Returns in Gulf Countries - Ahmad, Shabbir (International Journal of Energy Economics and Policy, 2019)
This study analyses the relationship between the stock market returns and the oil price volatility and its changes in six Gulf countries. We use changes in oil prices as shock while realized variance is used as proxy for volatility. After estimating an appropriate Vector Auto Regressive (VAR) model, use impulse response function and the Granger causality tests for the analysis. By employing weekly data starting from Jan-2008 to Jan-2017, study concludes that oil price variations and volatility impact the stock returns in all the Gulf stock markets. Keywords: GCC, Stock markets, Oil price shocks, Impulse response function, Granger Causality test JEL Classifications: G12; Q43; G10; C32 DOI: https://doi.org/10.32479/ijeep.7837